Аналіз теплообмінних процесів у системі «метал — протипригарне покриття — заморожена форма» - Замятін, М.І.; Лисенко, Т.В.; Тур, М.П.; Данілова, К.О. (Physico-technological Institute of Metals and Alloys, 2024)
The article is devoted to the analysis of heat exchange processes in the "metal — non-stick coating — frozen mold" system, which is an important aspect of research in the field of materials science and industrial technology, as it affects the quality and efficiency of the final product. The study also paid special attention to the processes of heat exchange between the metal, the non-stick coating and the frozen mold thanks to the analysis of the obtained indicators, calculated and experimental data. In addition, it is necessary to take into account the interaction between the various elements of the system, such as the thermodynamic properties of the coating and the thermal insulation properties of the frozen mold. One of the key aspects of the analysis was taking into account the heat capacity and thermal conductivity of the materials that make up the system, since heat capacity indicates the ability of a material to absorb heat, and thermal conductivity determines its ability to transfer heat. The properties of the non-stick coating, which protects the metal from high temperatures and provides optimal conditions for freezing the mold, are considered, since they can affect heat exchange by reducing or increasing the contact between the metal and the frozen mold. Based on the obtained data, a nomogram was constructed to determine the minimum thickness of the frozen rod depending on the thickness of the casting wall and the cooling temperature of the mold. The developed mathematical model of the heat transfer process in the system is based on the method of cellular automata. The model adequately describes the real process and can be used for numerical studies. The results of the work provide an opportunity to help improve production technology and improve the quality of the final product thanks to the analysis of heat exchange processes in the "metal — non-stick coating — frozen mold" system.